Application of Magnetics Method to Mapping the Geothermal Source at Seulawah Agam Area - Asrillah Asrillah; Marwan Marwan; Ibnu Rusydy; Gartika Setiya Nugraha (Jurnal Natural, 2014)
Magnetic method had been employed at Seulawah Agam area in term of unveiling the potentially geothermal source. This method was carried out locally in both the geothermal filed of Heutsz’s Crater and Cempaga’s Crater where the locations are in Seulawah Agam slope which is included in Aceh Besar District. Geologically, the area is mainly controlled by volcanic mudflow and Lam Teuba’s rocks consisting of breccia, pumice and tuff and their age are from Tersier to Resen Period. The deployed equipment consisted of Magnetometer GSM-19T, Proton Sensors, Aluminum Stick, Connection Cable, GPS Antenna, Compass, and Watch. Portable GPS (Global Positioning System), Navigation type (map of the survey area), and complemented by the other technical equipment, such as handy talky, umbrella, pens and notes of observed data. This study was done by following two steps. At first, the base station was established as a reference point for all magnetic data of measurements. Furthermore, recording magnetic data at each point by repeating three times until the last point by following the looping pattern as pathway of measurement both in Heutsz’s crater whose nine point recordings and in Cempaga’s crater whose seventeen points was consecutively done. The data were simply processed by using Microsoft excel that can just plot the magnetic anomaly and interpreted qualitatively being preliminary research. The result showed that at the north pathway had high magnetic anomaly of rocks located at B6 point and it was assumed as the area having the economically mineral in fracture zones. The rocks with low a anomaly value were obtained at –F125 BR is suggested as the thermal sources while at the South pathway from observing station till the Cempaga’s crater was obtained the geological structure as the Sumatran Fault of Aceh’s segment at CK4 point and this finding showed similar correlation with the result of gravity survey at same pathway published in another paper. In conclusion, this method effectively showed that the Seulawah Agam has potency as thermal source.